Higher-order thinking skills-based science literacy questions for high school students - Luzyawati, Lesy; Hamidah, Idah; Fauzan, Aditya; Husamah, Husamah (Journal of Education and Learning (EduLearn), 2025)
Students' science literacy abilities must receive special attention, particularly by investigating root causes and implementing strategies for improvement. Measuring science literacy through questions is crucial to determine students’ proficiency to be science literate. This research aims to produce higher-order thinking skill (HOTS)-based science literacy questions that are feasible (valid and reliable) to measure high school students' science literacy on respiratory system material. This research employed research and development (RD) approach. This study involved 300 senior high school students across Indonesia. Research data was analyzed using confirmatory factor analysis (CFA). The empirical study revealed 20 HOTS-based science literacy questions on respiratory system material with acceptable reliability values. These results show the feasibility of the developed questions and highlight the possibility for further extensive trial stage to assess students' science literacy.